68Ga-FAPI PET/CT in Assessment of Leptomeningeal Metastases in a Patient With Lung Adenocarcinoma. (October 2020) - Hao, Bing; Wu, Jingxun; Pang, Yizhen; Sun, Long; Chen, Haojun
Abstract : Abstract: We presented a case of 64-year-old woman with pathologically diagnosed lung adenocarcinoma. Brain metastases were highly suspected due to the appearance of neurological symptoms. However, no abnormal finding in the brain was observed on 18 F-FDG PET/CT. Contrast-enhanced MRI showed the presence of leptomeningeal metastases but with a negative cerebrospinal fluid analysis. For this reason, the patient underwent 68 Ga-FAPI PET/CT, later fused with MRI scans that showed intense uptake of 68 Ga-FAPI in leptomeningeal regions correspondent to the sites of gadolinium enhancement. This case highlights that 68 Ga-FAPI would be promising for the identification of leptomeningeal involvement in patients with malignant disease.